A finite-time safety-critical control based on barrier Lyapunov function for autonomous surface vessels - Cao, Văn Bính; Đàm, Văn Tùng; Phạm, Văn Triệu (Journal of Transportation Science and Technology, 2026)
In recent years, ensuring the stability and safety of unmanned surface vessels in complex marine environments has become a critical challenge in the research and development of control strategies. In this paper, a finite-time safety-critical control method is proposed to ensure the accurate and stable operation of surface vessels. Firstly, a backstepping-based controller integrated with a Lyapunov barrier function is developed to maintain the system in a safe working space. Next, the stability of the closed-loop system is rigorously demonstrated based on the Lyapunov stability theory. In addition, the convergence time of tracking errors is explicitly derived, facilitating the operator to adjust the control parameters according to the specific requirements of practical applications. Finally, the effectiveness of the method is verified through numerical simulation results and compared with several existing state-of-the-art controllers, confirming the feasibility and reliability of the proposed method
Keywords: Safety-critical control; Finite-time control; Lyapunov stability; Surface vessels